Pengaruh atribut supermarket dan motif belanja hedonik terhadap loyalitas konsumen melalui motif belanja utilitarian pada supermarket giant ekspress - Maria Kristina; Syarifah Hudayah; J. Kuleh (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
The purpose of this study was to determine how much influence indicator supermarket attribute (the atmosphere, the location, facilities, service salesman, merchandise) and hedonic shopping motives together on customer loyalty through a utilitarian shopping motives variables. How to create customer loyalty is high with attention to the motive of shopping from a consumer who wants to shop at Giant supermarket Ekspress. Where this research using an analysis tool Partial Least Square.  Supermarket attribute positive effect on Motive Shopping Ultilitiran. This is evidenced by the results of the original value estimete LS sample amounted to 0,311 with significance below 5% showed with 3,646 tstatistik greater than t-table value of 1.962. LS estimete original sample value is equal to 0227 with significantly below 5% as indicated by the value of the T-statistic greater than 2742 t-table value of 1.962. The value of the original sample positive estimate indicates that hedonic shopping motives positive effect on Motive Shopping Ultilitiran LS estimete original sample value is equal to 0557 with significantly below 5% as indicated by the value of the T-statistic greater than 8336 t-table value of 1.962. The value of the original sample positive estimate indicates that the motive of shopping ultilitiran positive effect on customer loyalty. Estimete original sample value is equal to 0173 with significantly below 5% as indicated by the value of the T-statistic greater than 3,162 t-table value of 1.962. The value of the original sample positive estimate indicates that the attribute Supermarket positive effect on customer loyalty.